"Dwaj święci" Aleksandra Kuprina: Studium przypadku - Krynicka, Tatiana (Colloquia Litteraria, 2024)
Aleksandr Kuprin is considered to be a penetrating and wise observer of human life, admirer of colourful characters which represent different social groups, a writer who is able to transgress the borderlines of literary conventions in order to reveal fundamental truthes of the human existence. The tale Two saints proves these statements to be true. Its main heroes are Nicholas, bishop of Myra and John Cassian. Following the plot of the Russian folk legend, A. Kuprin depicts their journey in common to the Heavens, skilfully approximates both ancient saints to his reader and demonstrates different ways that lead to God, whose Justice is Mercy.